Selenium supplementation prevents DNA damage in RAM spermatozoa - Moya, Carla Fredrichsen; Piagentini, Marcelo; Silva, Danilo da Cunha; Fernandes, Fábio Henrique [UNESP]; Salvadori, Daisy Maria Fávero [UNESP]; Oba, Eunice [UNESP] (FapUNIFESP (SciELO), 2021)
In the present study, we aimed to evaluate the effects of different concentrations of selenium (Se) ovine nutritional supplementation on spermatozoa DNA integrity. Thirty male ovines (age: 10 months) were used. They were fed with hay and ram food in an intensive system, which was divided into stalls (5 m long and 3 m wide) with feeding troughs, and had ad libitum access to food and water. Ovines in group 1 (G1, the negative control) received mineral salt supplementation without Se; ovines in G2 received the same mineral salt mixed with 5 mg Se (as sodium selenite)/kg mineral supplement;ovines in G3 received 10 mg Se/kg mineral supplement; ovines in G4 received 15 mg Se/kg mineral supplement; and ovines in G5 received 20 mg Se/kg mineral supplement. Ovines in all groups remained untreated for 14 days, followed by a treatment period of 56 days. Semen samples were obtained by electroejaculation. The DNA damage in semen samples was evaluated using the comet assay. The experimental design was implemented using a 5 × 5 Latin Square, i.e., five treatments and five experimental periods. The mean differences were compared using Tukey’s test at a significance level of 5%. The control group (G1) showed a high percentage of DNA damage compared to the Se-treated groups (G2–G5). Therefore, Se supplementation could decrease the basal level of DNA damage in sperm cells, suggesting that Se might exert protective effects on sperm DNA.
Suplementação com selênio previne danos ao DNA espermático de ovinos
Keywords: Chemoprevention; Comet assay; Ovine; Semen